(untitled) (Linguostylistic Studies, 2017)
The article reveals the essence of the notion of «publicistic discourse», describes the main genre and thematic varieties of the publicistic works by Mykhailo Hrushevskyi written in 1918-1919. The emphasis is laid on the pragmatic orientation of them as a socio- evaluative speech acts. The author identifies the principal linguistic means used to express the axiological rationality in the publicistic discourse. The peculiarities of functioning of both colloquial and bookish phraseology are considered as a productive means of explicating the evaluation issues in the Mikhailo Hrushevskyi’s publicistic discourse. The study reveals phraseologisms, which express a positive evaluation, and those with a negative evaluating meaning. The importance is placed on the description of the main ways of the individual author’s transformations of the phraseological units (axiological re-thinking of the content of phrases, individual author variations of the component composition of phraseological units).